Investigation of polymer-based BaO and rGO nanocomposites for application in low energy X ray attenuation (Brazilian Journal of Radiation Sciences, 2019)
Polymeric materials can serve as a matrix for the dispersion of nanomaterials with good attenuation features, resulting in lightweight, conformable, flexible, lead-free and easy-to-process materials. Thus, some well-known radiation shielding materials could be used in low proportion as a filler, for the formation of new materials. On the other hand, nanostructured carbon materials, such as graphene oxide (GO) have been reported recently to show enhanced attenuation properties. For the present work, poly(vinylidene fluoride) [PVDF] homopolymers and its fluorinated copolymers were filled with metallic oxides and nanosized reduced graphene oxides (rGO) in order to produce nanocomposites with increased low energy X ray attenuation efficiency. We objective is to investigate the X ray shielding features of multilayered PVDF/rGO and P(VDF-TrFE)/BaO composites. PVDF/rGO overlapped with P(VDF-TrFE)/BaO thin films were sandwiched between two layers of kapton films of different thickness. The linear attenuation coefficients were measured for monochromatic X ray photons with energy of 8.1 keV. The samples were characterized by Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Ultraviolet–visible (UV-vis) and Fourier-Transform Infrared (FTIR) Spectroscopy. The linear attenuation coefficient of the multilayered sample was evaluated and compared with the linear attenuation of the individual constituents. It was observed an increase in the attenuation coefficient of the overlapping samples. It is demonstrated that thin films of rGO nanocomposite with thickness of only 0.32 mm can attenuate up to 50% of X ray beams with energy of 8.1 keV, justifying further investigation of these nanocomposites as X ray or gamma radiation attenuators